2008
DOI: 10.1007/s00005-008-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Current advances in the management of urticaria

Abstract: Urticaria is a relatively common autoimmune/autoreactive skin disorder that may severely impair quality of life. Although rarely life-threatening, widespread urticaria and its associated angioedema can be an extremely disabling and difficult-to-treat condition. Patients may suffer symptoms such as pruritus and disfigurement due to wheals for years or decades. Urticaria is caused by cutaneous mast-cell degranulation attributed to immunological, non-immunological, and idiopathic causes. The last decade has seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…The study of Zuel-Fakkar et al reported that Blastocystis hominis was found in 60.6% of patients with urticaria, whereas no parasite was isolated in healthy controls [8]. In general, urticaria is a very common skin disorder that can have immune, non-immune or idiopathic causes [9]. The idiopathic urticaria is accounted for in 75% of all urticaria cases [10].…”
Section: Introductionmentioning
confidence: 99%
“…The study of Zuel-Fakkar et al reported that Blastocystis hominis was found in 60.6% of patients with urticaria, whereas no parasite was isolated in healthy controls [8]. In general, urticaria is a very common skin disorder that can have immune, non-immune or idiopathic causes [9]. The idiopathic urticaria is accounted for in 75% of all urticaria cases [10].…”
Section: Introductionmentioning
confidence: 99%
“…The basophil histamine release assay is the "gold standard" for detecting functional autoantibodies in the serum of patient with chronic urticaria. The finding that peripheral blood basophils are reduced or absent in patients with chronic urticaria histamine-releasing autoantibodies suggests that chronic urticaria has an autoimmune origin [15].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Urticarial transfusion reactions occur when allergenic substances in the plasma of the donated blood product react with preexisting IgE antibodies in the recipient. Certain drugs (opioids, vecuronium, vancomycin, and others) as well as radiocontrast agents cause urticaria due to mast cell degranulation through a non-IgE-mediated mechanism [12][13][14][15].…”
Section: Non-immune-mediated Urticariamentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the most common dermatologic problems and 20-30% of individuals have at least one attack of urticaria in their lifetime. [3][4][5][6][7] The most commonly used classification of urticaria is based on duration of its manifestations. When urticaria is present for less than six weeks, it is termed acute urticaria (AU).…”
Section: Introductionmentioning
confidence: 99%